2023
DOI: 10.1073/pnas.2216765120
|View full text |Cite
|
Sign up to set email alerts
|

Urban effects on local cloud patterns

Abstract: Urbanization extensively modifies surface roughness and properties, impacting regional climate and hydrological cycles. Urban effects on temperature and precipitation have drawn considerable attention. These associated physical processes are also closely linked to clouds’ formation and dynamics. Cloud is one of the critical components in regulating urban hydrometeorological cycles but remains less understood in urban-atmospheric systems. We analyzed satellite-derived cloud patterns spanning two decades over 44… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…Trees help mitigate the lethality [ 3 , 4 ] of the worsening urban heat island effect from climate change [ 5 ] through shading [ [6] , [7] , [8] ] and evapotranspiration [ 7 , 9 ]. The effects of these different cooling mechanisms vary across space and over time [ 10 , 11 ], and interact with other aspects of the built environment [ 8 , [12] , [13] , [14] , [15] ] and regional meteorology [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Trees help mitigate the lethality [ 3 , 4 ] of the worsening urban heat island effect from climate change [ 5 ] through shading [ [6] , [7] , [8] ] and evapotranspiration [ 7 , 9 ]. The effects of these different cooling mechanisms vary across space and over time [ 10 , 11 ], and interact with other aspects of the built environment [ 8 , [12] , [13] , [14] , [15] ] and regional meteorology [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Under cloudy conditions, the former effect is minimal and it is not well understood how much transpirational cooling persists under these conditions. Interestingly, it has been shown that cities even create clouds: they draw moisture in through advection and then a combination of turbulence from urban surface roughness and abundant urban aerosols create more clouds [ 16 ]. Excluding clouds prevents us from understanding the role of trees’ cooling under cloudy conditions.…”
Section: Introductionmentioning
confidence: 99%
“…of 10 associated with surface heating in urban areas can impact atmospheric dynamics, fostering the condensation of water vapor into clouds (Chen et al, 2011;Vo et al, 2023). Additionally, the augmented concentration of anthropogenic emissions in urban settings, stemming from industrial activities and vehicular traffic, introduces additional particulate matter and aerosols into the atmosphere (Z. H. Zhang et al, 2017).…”
Section: Our Results Unveil a Potential Mechanism That Explains The D...mentioning
confidence: 99%
“…Zhang et al, 2023), but also affects local weather patterns, such as enhancement of mean rainfall and short-duration extreme rainfall by increasing vertical uplift and moisture convergence (Ali et al, 2021;Fischer & Knutti, 2016;Y. Li et al, 2020;Liu & Niyogi, 2019;Vo et al, 2023). This amplifies the likelihood of "preconditioned" compound extremes, that is, the sequential occurrence of humid heatwaves and extreme rainfall (C. Li et al, 2023;W.…”
Section: Introductionmentioning
confidence: 99%